Technical and methodical aspects regarding certain flyaway moves on parallel bars - women - Neagu, G. (Science, Movement & Health, 2020)
The purpose of this article is to briefly present the main technical and methodical aspects of these dismounts.The dismount has the role of being a nodal element and a balancing point of the symmetry of the exercise on parallel bars. The dismount must be accompanied by valuable elements directly linked, which will bring an added value.